Features of “IN” prepositional phrases in the novel “ if tomorrow comes” by Sidney Sheldom and their Vienamese translation versions / Vũ Văn Độ; Supervisor: Ph.D Le Van Thanh - Vũ, Văn Độ
Prepositions and prepositional phrases are important components in any languages which are used to connect nouns or noun structures to other structures in a sentence. They exist in both English and Vietnamese language systems. However, prepositional phrases have different characteristics and usage in each language. This descriptive and qualitative study endeavored to explore the semantic and syntactic features of “IN” prepositional phrases in English and their Vietnamese translation versions. It involved the development of a bilingual corpus consisting of instance of sentences containing “IN” prepositional phrases extracted from the novel “If tomorrow comes” by Sidney Sheldom and their translation versions. The interpretive contrastive analysis was employed. It is expected that data analysis can produce meaningful conclusions concerning the similarities and differences in semantic and syntactic features of “IN” prepositional phrases in English and Vietnamese. Also, this research aims to identify and investigate on the use of “IN” prepositional phrases in English and Vietnamese. From there, this paper expects to provide implications for coaching prepositional phrases which may be useful for individuals who teach English or Vietnamese based on the identification of any potential problems caused by the characteristics of “IN” prepositional phrase.